2014
DOI: 10.1590/1806-9282.60.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends due to chronic obstructive pulmonary disease in Brazil

Abstract: Mortality trends due to chronic obstructive pulMonary disease in brazil rev assoc Med bras 2014; 60(3):255-261 255Original articleMortality trends due to chronic obstructive pulmonary disease in Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
2
2
1
5
Order By: Relevance
“…In 2014, smoking prevalence reduced to 10.8% (95% CI: 10.1–11.4%) in Brazilian capitals [ 33 ]. Rates are higher for males and females in Southern states, as found previously [ 34 ], probably due to smoking exposure as these states have the highest prevalence of smoking according to the Annual Surveys on Risk and Protective Factors for Chronic Diseases (VIGITEL) results [ 35 ]. This finding could be also related to improved data capture as completeness and quality of reporting is better in those states [ 7 ].…”
Section: Discussionsupporting
confidence: 61%
“…In 2014, smoking prevalence reduced to 10.8% (95% CI: 10.1–11.4%) in Brazilian capitals [ 33 ]. Rates are higher for males and females in Southern states, as found previously [ 34 ], probably due to smoking exposure as these states have the highest prevalence of smoking according to the Annual Surveys on Risk and Protective Factors for Chronic Diseases (VIGITEL) results [ 35 ]. This finding could be also related to improved data capture as completeness and quality of reporting is better in those states [ 7 ].…”
Section: Discussionsupporting
confidence: 61%
“…Better diagnosis might be the other potential cause of increase in the COPD‐specific mortality rate. The decline in COPD mortality rate is also reported in some other countries . Although in this study, the rate of mortality from COPD had increased in both sexes, the results of a study in England and Wales showed an increase in COPD mortality rate in females, but it reported a decrease in males .…”
Section: Discussioncontrasting
confidence: 49%
“…The latest statistics from COPD identify a gradual decline in some parts of the world in relation to morbidity and mortality. However, in Brazil, we found that the prevalence among adults and the elderly is significant (19%), which implies large economic and social expenditures, such as hospitalizations [46][47][48] . In the US, each exacerbation costs $88 to $7,757 19 .…”
Section: Discussionmentioning
confidence: 99%